Analysis of recovery strategies for construction and demolition waste in the last 10 years: a review of the scientific literature (LACCEI, 2024)
This article from the scientific literature talks about recovery strategies for construction and demolition waste (RCD) that have been used nationally and internationally in the last ten years in such a way that they serve as alternatives to the problem generated by these materials. leftovers present on public roads because there is no comprehensive plan or recovery strategies for this waste because they do not receive sufficient attention from the competent national authorities. This research aims to analyze RCD recovery strategies of the last ten years. A systematic review methodology was carried out using different scientific journals such as Scielo, Alicia, Redalyc, BASE, REDIB and DOAJ. On the other hand, 5 articles and 1 theses were discarded because they were not related to the objective of the study topic and were not within the last 10 years. Within the limitations, it was observed that there are not many countries that carry out studies on RCD recovery strategies. The country with the largest number of studies is Colombia, with Latin America having the highest number of studies. Finally, the valorization strategies that were used were identified, which are recycling, added material, construction of sheds, bioremediation of degraded soils, manufacture of concrete, bricks, paving stones, earth blocks, precast and concrete. It was possible to reach the conclusion that the most used strategy is recycling since it is a relatively widespread practice in several countries.